La formazione del fabbisogno di servizi reali all’internazionalizzazione: un modello knowledge-based - Vignola, Marina; Marchi, Gianluca (Piccola Impresa / Small Business, 2012)
Starting from the recognition of firm’s knowledge gaps, this explorative study investigates the formation of needs for internationalization assistance. Drawing on Erikssson et al. (1997), the international knowledge accumulation process is analyzed. The aim is to shed light on how the role of different knowledge constructs varies in relation to the decision frame complexity and the related impact on demand for assistance programs. We test the hypotheses on a sample of 108 internationalized firms. Findings suggest that new service models, in support of firm’s internationalization, are to be based on a deeper understanding about how the international knowledge develops and changes along its accumulation process. These models are helpful to drive and favor the internationalization processes of SMEs.